The Paradigm of Zakarpatya Greek Catholic Church of Ukrainian National Consciousness Development (1771–1867) - Rozlutska, Galyna; Sokol, Mariana (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Nowadays under the influence of external dynamic factors, the gap between Ukrainians and the spiritual traditions of the Ukrainian nation is widening. Globalization, internationalization and technologicalization are contributing to the spread of alien ideologies in the Ukrainian society that give rise to the formation of a mercantile-pragmatic outlook in the younger generations. The need for constructive-critical rethinking of the experience of the past and creative interpretation of its positive achievements in the construction of qualitatively new strategies for the spiritual healing of the Ukrainian nation is exacerbated. The aim of the article is to link the influence of the Greek Catholic Church on the formation of the national consciousness of the population of Transcarpathia between 1771 and 1867; identify the socio-historical factors behind the formation of the Greek Catholic Church in Transcarpathia in the context of nationalization; to analyze the cultural, educational and organizational-pedagogical activities of the Greek Catholic clergy. To achieve this goal, the following methods have been used: аnalytical and synthetic methods to analyze the source of the study; the problem-chronological method for the coverage of historical events and processes in the ontogenetic development of the ideology of the Greek Catholic Church; comparative-historical method for comparing historical facts and phenomena, revealing their characteristic features; manifestations in the cultural-educational, pedagogical activity of the Greek Catholic clergy. The scientific novelty of the obtained results is that the socio-political and socio-cultural conditions of the Greek Catholic Church in Transcarpathia in 1771–1867 have been revealed. The leading role of the Greek Catholic Church in national consciousness formation of Transcarpathian Ukrainians, which was structured due to the institutional design of the church, has been identified. The main ideological and political transformations of the Greek Catholic clergy in search of their national nature have been analyzed. On the basis of the analysis of historical events of the period from 1771 till 1867 in the development of the Greek Catholic Church in Transcarpathia it can be outlined the main results of the study such as the isolation of positive features, in particular, the canonization of Mukachevo and Prešov Dioceses, the increasing number of parishes and believers and the falls and negative aspects like manifestations of madyarization. It has been proved that the institutional registration of the church became an effective mechanism of self-identification of Transcarpathian Ukrainians through the preservation of the Church Slavonic language in liturgical services and its support in Hungarian environment. It has been found that national ideas crystallized in the environment of patriotic priests, which, under the pressure of socio-political influences of that era, sought to find their nationality in various ideological directions: Moscow, Austrophil, etc. The conducted research makes it possible to conclude that the institutional design of the Greek Catholic Church in Transcarpathia is conditioned by socio-historical influences, the canonization of Mukachevo and Prešov Dioceses, the increase in the number of parishes and parishioners in the period 1771–1867.